Erosion rate study at the Allchar deposit (Macedonia) based on radioactive and stable cosmogenic nuclides (26Al, 36Cl, 3He, and 21Ne). (14th February 2016) - Pavićević, M. K.; Cvetković, V.; Niedermann, S.; Pejović, V.; Amthauer, G.; Boev, B.; Bosch, F.; Aničin, I.; Henning, W. F.
Abstract: This paper focuses on constraining the erosion rate in the area of the Allchar Sb‐As‐Tl‐Au deposit (Macedonia). It contains the largest known reserves of lorandite (TlAsS2 ), which is essential for the LORanditeEXperiment (LOREX), aimed at determining the long‐term solar neutrino flux. Because the erosion history of the Allchar area is crucial for the success of LOREX, we applied terrestrial in situ cosmogenic nuclides including both radioactive ( 26 Al and 36 Cl) and stable ( 3 He and 21 Ne) nuclides in quartz, dolomite/calcite, sanidine, and diopside. The obtained results suggest that there is accordance in the values obtained by applying 26 Al, 36 Cl, and 21 Ne for around 85% of the entire sample collection, with resulting erosion rates varying from several tens of m/Ma to ∼165 m/Ma. The samples from four locations (L‐8 CD, L1b/R, L1c/R, and L‐4/ADR) give erosion rates between 300 and 400 m/Ma. Although these localities reveal remarkably higher values, which may be explained by burial events that occurred in part of Allchar, the erosion rate estimates mostly in the range between 50 and 100 m/Ma. This range further enables us to estimate the vertical erosion rate values for the two main ore bodies Crven Dol and Centralni Deo. We also estimate that the lower and upper limits of average paleo‐depths for the ore body Centralni Deo from 4.3 Ma to the present are 250–290 and 750–790 m, respectively, whereas the upper limit of paleo‐depth for the ore body Crven Dol over the same geological age is 860 m. The estimated paleo‐depth values allow estimating the relative contributions of 205 Pb derived from pp‐neutrino and fast cosmic‐ray muons, respectively, which is an important prerequisite for the LOREX experiment. Key Points: Erosion rate of a unique Tl‐deposit is studied by radioactive/stable nuclides The vertical erosion rate is obtained for the locations with most Tl‐rich ore The study contributes to determining the long‐term average flux of solar pp‐neutrinos